Ge‐Doped ZnSb/β‐Zn4Sb3 Nanocomposites with High Thermoelectric Performance. Issue 18 (10th July 2019) - Ostovari Moghaddam, Ahmad; Shokuhfar, Ali; Zhang, Yu; Zhang, Ting; Cadavid, Doris; Arbiol, Jordi; Cabot, Andreu
Abstract: ZnSb/β‐Zn4 Sb3 nanocomposites are produced from Zn1.1− x Ge x Sb mixtures using a two‐step process. First, proper amounts of the three elements are mixed, melted, and reacted at 800 K. During this process, the nonstoichiometric mixture is crystallized in a combination of ZnSb and β‐Zn4 Sb3 phases. Then, the material is ball milled and subsequently hot pressed. Through this process, a dense ZnSb/β‐Zn4 Sb3 composite, consisting of β‐Zn4 Sb3 nanoinclusions embedded within a ZnSb matrix, is formed. The particular phase distribution of the final ZnSb/β‐Zn4 Sb3 composites is a consequence of the harder and more brittle nature of ZnSb than Zn4 Sb3, which translates into a stronger reduction of the size of the ZnSb crystal domains during ball milling. This small particle size and the high temperature generated during ball milling result in the melting of the ZnSb phase and the posterior crystallization of the two phases in a ZnSb/β‐Zn4 Sb3 matrix/nanoinclusion‐type phase distribution. This particular phase distribution and the presence of Ge result in excellent thermoelectric performances, with power factors up to 1.5 mW m −1 K −2, lattice thermal conductivities down to 0.74 W m −1 K −1, and a thermoelectric figures of merit, ZT, up to 1.2 at 650 K, which is among the highest ZT values reported for ZnSb. Abstract : The in situ preparation of ZnSb/β‐Zn4 Sb3 nanocomposites through a novel route is investigated. This approach leads to an outstanding high and stable ZT value of 1.2 for Ge‐doped ZnSb/β‐Zn4 Sb3 nanocomposite, which is among the highest values reported for this material.